The 4D Model in Developing Nearpod-Based Interactive Media for Reflection Material - Nuniek Noermala; Iyan Rosita Dewi Nur (PRISMA, 2026)
Mathematics plays an important role in developing logical, critical, creative, and systematic thinking skills, but it is often considered difficult and boring, requiring innovative learning media. One of the most challenging topics is reflection because of its abstract nature and the need for visualization skills. This study aims to develop interactive media based on Nearpod that is valid, practical, and effective. The method used is Research and Development (R&D) with the 4D model (Define, Design, Develop, Disseminate) and a one-group pretest–posttest design on 35 students in grade XI at Karawang State Senior High School 6, who were selected using purposive sampling. Data were obtained through validation questionnaires, practicality questionnaires, and learning outcome tests. The results showed that Nearpod media was rated as very feasible by media experts, with an overall average score of 3.90. It was also rated as very feasible by subject matter experts, with an overall average score of 3.80, and by students, with an overall average score of 3.85. In terms of practicality, it was categorized as highly feasible based on the results of the teacher questionnaire assessment with an overall average score of 3.60, while based on the student questionnaire assessment, it was categorized as feasible with an overall average score of 3.44. Thus, Nearpod is proven to be valid and practical for use in reflection material.